The inhibitory combustion reaction performance and tail gas analysis of composite ultra-fine dry powder extinguishing agent containing different additives. (May 2020) - Guo, Xinxin; Pan, Xuhai; Zhang, Lijing; Hua, Min; Li, Hangchen; Li, Shunchao; Zhang, Han
Abstract: For lack of an extinguishing agent with high-efficiency, non-toxic and environmentally friendly, a new type of extinguishing agent was fabricated to solve such an urgent problem. In this study, the zinc borate (ZB) and ferrocene (Fe(Cp)2 ) were utilized as two additives for extinguishants to suppress combustion reaction and the toxicity of the tail gas was detected. The mass fraction of ZB corresponding to the optimal inhibitory effect was determined to be 0.5–1.5%, by contrast, the optimum interval of Fe(Cp)2 was detected as 0.5–1.0%. Similarly, with the increasing proportion of the two additives, the homologous inhibitory action was gradually weakened. From the perspective of thermogravimetric analysis (TGA), it was indicated that the ZB accelerated the pyrolysis process of the extinguishant, making its thermal decomposition process more thoroughly. Meanwhile, the differential scanning calorimetry (DSC) demonstrated that the decomposition efficiency was markedly improved when the amount of ZB was maintained at 0.5–1.5%. Besides, the tail gas tests were implemented to assess the extent of toxic and harmful properties. In terms of the carbon monoxide (CO) and carbon dioxide (CO2 ) generated, once the mass fraction of ZB and Fe(Cp)2 was less than 1.5% and 1.0% respectively, the concentration of CO and CO2 was distinctly lower than that without additives. Moreover, the inhibitory ability on nitrogen oxides (NOx) was enhanced when the mass fraction of the two additives was kept below 1.0%. The results confirmed that a more practical extinguishant was proposed and it can provide guidance for the application and development of extinguishants. Highlights: The zinc borate and ferrocene were selected to suppress flame and their suppression efficiency was compared. The thermal decomposition performance of extinguishants were implemented to compare with the inhibition performance. The study compared the effects of extinguishants containing different additives on tail gas (CO, CO2, NOx) concentration. A practical extinguishant was proposed and it can provide guidance for the application and development of extinguishants.